2021
DOI: 10.1111/ijn.12920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self‐management programs on blood pressure, self‐efficacy, medication adherence and body mass index in older adults with hypertension: Meta‐analysis of randomized controlled trials

Abstract: Aim To assess the effects of self‐management interventions on systolic blood pressure, diastolic blood pressure, self‐efficacy, medication adherence and body mass index in older adults with hypertension. Background Effective treatment of hypertension may require the practice of self‐management behaviours. However, evidence on effects of self‐management interventions on blood pressure, self‐efficacy, medication adherence and body mass index in older adults with hypertension is lacking. Design A systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
4
7
0
1
Order By: Relevance
“…The partial mediating effect of SLE on the prospective reciprocal relationships between self-perceived disease control and these self-management behaviours accounted for only 37.11, 25.88, and 19.39% of the total effect of self-perceived disease control on medication use, self-monitoring and physical activity, respectively. Moreover, consistent with previous studies [ 20 , 50 , 79 , 80 ], our results proved that the significant effectiveness of medication therapy in disease control led to the strongest predictive effects of self-perceived disease control and SLE for medication use; middle-aged and older hypertensive patients are more likely to adhere to self-monitoring behaviour than they are to physical activity. The reason may be that medication use is the most timely and effective way to control hypertension among all self-management behaviours [ 81 , 82 ], and self-monitoring behaviour is easy to adhere to because self-monitoring requires less effort than physical activity [ 83 ].…”
Section: Discussionsupporting
confidence: 91%
“…The partial mediating effect of SLE on the prospective reciprocal relationships between self-perceived disease control and these self-management behaviours accounted for only 37.11, 25.88, and 19.39% of the total effect of self-perceived disease control on medication use, self-monitoring and physical activity, respectively. Moreover, consistent with previous studies [ 20 , 50 , 79 , 80 ], our results proved that the significant effectiveness of medication therapy in disease control led to the strongest predictive effects of self-perceived disease control and SLE for medication use; middle-aged and older hypertensive patients are more likely to adhere to self-monitoring behaviour than they are to physical activity. The reason may be that medication use is the most timely and effective way to control hypertension among all self-management behaviours [ 81 , 82 ], and self-monitoring behaviour is easy to adhere to because self-monitoring requires less effort than physical activity [ 83 ].…”
Section: Discussionsupporting
confidence: 91%
“…3 After selfmanagement support, it was determined that there was a significant decrease in the blood pressure of patients in the intervention group, and the mean blood pressure values measured by the researcher were in the normal classification according to the ESC Guidelines for the Management of Arterial Hypertension. 3 The results of our study are consistent with the results of other studies in the literature and show that self-management support 16,32,33 , and disease-specific education 25,34,35 have a significant effect on decreasing systolic and diastolic blood pressure values.…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrating participants in the web‐based self‐care program had significant improvements in self‐efficacy and self‐care strengthen previous findings showing individualized health education intervention has been demonstrated to be beneficial for enhancing self‐efficacy of achieving blood pressure control (Van Truong et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…The effect of self‐efficacy on medication adherence for participants in the intervention group echo the results of a meta‐analysis of 12 randomized controlled trials by Van Truong et al (2021), which showed self‐care management programs facilitate medication adherence for older adults with hypertension. Sevick et al (2018) suggested the challenge of changing a person's lifestyle is to construct new knowledge and skills in such a way that barriers can be overcome without too much effort.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation